Multi-proxy records for the Early Pleistocene interval of Marine Isotope Stage (MIS) 48 to MIS 74 (1.46-1.94 Ma) from IODP Site U1387 in the Gulf of Cadiz - Voelker, Antje H L; Ducassou, Emmanuelle; Acton, Gary D; Richter, Carl; Alberto, Ana; Kuhnert, Henning (PANGAEA, 2025)
Using sediment samples from IODP Hole U1387C, we explored the Early Pleistocene history of the upper Mediterranean Outflow Water (MOW) core above the central Faro Drift in the Gulf of Cádiz. The time series of benthic foraminifer stable isotope and grain size related data for the interval of cores U1387C-8R to U1387C-19R have a rigorous stratigraphic framework consisting of nannofossil biostratigraphy and paleomagnetic and δ18O stratigraphy. The grain size data includes the different size fractions, %D90 and sortable silt. Inclination and declination data for the paleomagentic stratigraphy is also provided. In addition, LR04 stack related age models for the Early Pleistocene sequences of ODP Site 975 and IODP Site U1389, used for comparison in the study, are included.
Keywords: Contourites; early Pleistocene; Gulf of Cadiz; IODP Site U1387; MOW